Low maternal vitamin D status in pregnancy increases the risk of childhood obesity. Issue 8 (28th January 2018) - Daraki, V.; Roumeliotaki, T.; Chalkiadaki, G.; Katrinaki, M.; Karachaliou, M.; Leventakou, V.; Vafeiadi, M.; Sarri, K.; Vassilaki, M.; Papavasiliou, S.; Kogevinas, M.; Chatzi, L.
Summary: Background: Vitamin D may modulate adipogenesis. However, limited studies have investigated the effect of maternal vitamin D during pregnancy on offspring adiposity or cardiometabolic parameters with inconclusive results. Objectives: The objective of this study is to examine the association of maternal 25(OH)‐vitamin D [25(OH)D] status with offspring obesity and cardiometabolic characteristics in 532 mother–child pairs from the prospective pregnancy cohort Rhea in Crete, Greece. Methods: Maternal 25(OH)D concentrations were measured at the first prenatal visit (mean: 14 weeks, SD: 4). Child outcomes included body mass index standard deviation score, waist circumference, skin‐fold thickness, blood pressure and serum lipids at ages 4 and 6 years. Body fat percentage was also measured at 6 years. Body mass index growth trajectories from birth to 6 years were estimated by mixed effects models with fractional polynomials of age. Adjusted associations were obtained via multivariable linear regression analyses. Results: About two‐thirds of participating mothers had 25(OH)D concentrations <50 nmol L −1 . Offspring of women in the low 25(OH)D tertile (<37.7 nmol L −1 ) had higher body mass index standard deviation score ( β 0.20, 95% CI: 0.03, 0.37), and waist circumference ( β 0.87 95% CI: 0.12, 1.63) at preschool age, compared with the offspring of women with higher 25(OH)D measurements (≥37.7 nmol L −1 ), on covariate‐adjusted analyses. The observed relationships persisted at age 6 years. We found no association between maternal 25(OH)D concentrations and offspring blood pressure or serum lipids at both time points. Conclusions: Exposure to very low 25(OH)D concentrations in utero may increase childhood adiposity indices. Given that vitamin D is a modifiable risk factor, our findings may have important public health implications.